Influence of Brand Image on Purchase Intention in the Context of Modern Consumer Behavior in Skincare Products. - Fadhil Orizea Ananda; Nofanolo Gulo; Gusti Ngurah Made Arya Bagus Saputra (Lentera Jurnal Pengabdian Masyarakat, 2026)
This study aims to examine the influence of Brand Image on Purchase Intention in the skincare industry by analyzing the roles of Consumer Trust, Perceived Quality, and Brand Attitude. The study applied a quantitative research approach using a survey method. Data were collected through online questionnaires distributed to consumers who had purchased skincare products within the last six months. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that Brand Image significantly influences Perceived Quality, indicating that consumers who perceive skincare brands positively are more likely to evaluate product quality favorably. Consumer Trust and Perceived Quality also demonstrate strong relationships with Purchase Intention, suggesting that trust and perceived quality are important determinants of consumers’ buying behavior. However, Brand Image does not significantly influence Consumer Trust and Brand Attitude. In addition, Brand Attitude does not significantly affect Purchase Intention. These results suggest that modern skincare consumers prioritize product effectiveness, safety, transparency, and online reviews rather than relying solely on brand reputation when making purchasing decisions.